Elucidating the formation pathway of photo-generated asphaltenes from light Louisiana sweet crude oil after exposure to natural sunlight in the Gulf of Mexico. (December 2020) - Wang, Qing; Leonce, Burke; Seeley, Meredith Evans; Adegboyega, Nathaniel F.; Lu, Kaijun; Hockaday, William C.; Liu, Zhanfei
Highlights: Light Louisiana sweet crude oil was photooxidized for 44 d with natural sunlight. SARA fractions of weathered oil were analyzed by pyrolysis GC–MS and NMR. Photo-generated asphaltenes were mainly sourced from the aromatic fraction. Photo-generated asphaltenes had small aromatic cores and long alkyl tails. Intact n -alkanes were occluded into native and photo-generated asphaltenes. Abstract: Photooxidation was an important weathering process for spilled oil at the water surface following the Deepwater Horizon oil spill, leading to the rapid formation of polar or oxygenated hydrocarbons, or photo-generated asphaltenes. While the great extent and rapid time scale of this process have been well documented, little is known about the formation pathways and chemical structures of photo-generated asphaltenes. To address this knowledge gap, we conducted a 44-day natural sunlight exposure experiment using Louisiana light sweet crude oil amended in seawater. The saturate, aromatic, resin and asphaltene fractions were separated and quantified by adsorption chromatography. Molecular details were obtained by thermal slicing ramped pyrolysis-gas chromatography–mass spectrometry, while bulk structural changes were quantified by 13 C solid-state nuclear magnetic resonance. These analyses illustrate that, in comparison to the "native" petrogenic asphaltenes in crude oil, photo-generated asphaltenes had larger bridged-island structures with smaller aromatic cores and longer alkyl tails in each island. Our results also demonstrated that the large aliphatic fraction of the photo-generated asphaltene was sourced from the alkyl moieties of the aromatic fraction rather than the saturate fraction. A group of intact hydrocarbons, predominantly n -alkanes (C16 –C28 ), was occluded in both native and photo-generated asphaltene matrices. Overall, these results provide insight into the formation mechanisms and structural details of photo-generated asphaltenes in oils after exposure to natural sunlight in Gulf of Mexico waters. This knowledge is valuable for developing remediation strategies for oil spills, in particular those under strong solar irradiance.